Strange Loyalties - McIlvanney W. William (London, Sceptre, 1992)
When Jack Laidlaw`s brother is killed in a road accident, the maverick Glasgow Inspector takes a week off work to find out for himself what happened - not, at first, because he suspects foul play, but because he had the impression all was not well in his brother`s life.